Human Resource Development in SMEs within the European Social Fund in Poland – research findings and international perspective - Tracz-Krupa, Katarzyna; Tomé, Eduardo (Rozwój zasobów ludzkich w MŚP ze środków Europejskiego Funduszu Społecznego (EFS) – wyniki badań empirycznych i perspektywa międzynarodowa, 2019)
The paper aims to examine the Human Resource Development (HRD) in small and medium enterprises (SMEs) funded by the European Social Fund (ESF) in Poland between 2007 and 2013. The research is based on theories that support HRD investment specifically in SMEs, and uses the Human Capital Theory (HCT) with some extensions. The paper addresses the question of public support in HRD and international support for development purposes. Finally it stresses that the support may have national and international implications. The research methodology involved a series of computer assisted telephone interviews (CATI) in a sample of 44 SMEs that received EU funding for HRD. It also included computer assisted personal interviews (CAPI) with experts in the ESF, participant observation and analysis of the project documentation. The findings indicate that the ESF effort of international scope had a positive impact in Polish SMEs
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 2, s. 26-40
Keywords: human resource development; SMEs; European Social Fund; Poland; rozwój zasobów ludzkich; MŚP; Europejski Fundusz Społeczny; Polska